2017
DOI: 10.1139/cjpp-2016-0664
|View full text |Cite
|
Sign up to set email alerts
|

The role of damage- and pathogen-associated molecular patterns in inflammation-mediated vulnerability of atherosclerotic plaques

Abstract: https://mc06.manuscriptcentral.com/cjpp-pubs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 99 publications
1
52
0
1
Order By: Relevance
“…Of note, the same mediators are also known to be linked to endothelial dysfunction and vascular calcification in other inflammatory diseases such as autoimmune diseases, inflammatory bowel syndromes, and rheumatoid arthritis. Cytokines and mediators including TNF-α, IL-1β, IL-6, and IFNγ, along with MMP, are also responsible, upon stimulation, of the destabilization of atherosclerotic plaques, leading to ischemic events (96).…”
Section: The Role Of Inflammatory Cytokines In the Pathogenesis Of Atmentioning
confidence: 99%
“…Of note, the same mediators are also known to be linked to endothelial dysfunction and vascular calcification in other inflammatory diseases such as autoimmune diseases, inflammatory bowel syndromes, and rheumatoid arthritis. Cytokines and mediators including TNF-α, IL-1β, IL-6, and IFNγ, along with MMP, are also responsible, upon stimulation, of the destabilization of atherosclerotic plaques, leading to ischemic events (96).…”
Section: The Role Of Inflammatory Cytokines In the Pathogenesis Of Atmentioning
confidence: 99%
“…At the same time, pro‐inflammatory mediator production by PAMP‐stimulated host cells underlies a variety of disorders. It is now widely accepted that the initiation and progression of atherosclerotic lesions involves both sterile and infectious chronic inflammatory responses . Although the molecular mechanisms underlying the pathogenesis of rheumatoid arthritis are not fully understood, there is increasing evidence that activation of PRRs, as well as infections by many microorganisms, might play an important role in the maintenance of inflammation in rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…4 Accumulating evidence has shown that arterial walls thickening, the formation of atherosclerotic plaques and vascular stenosis were significant risk factors for ischemic cerebrovascular disease. 6 Although most subtypes of ischemic stroke share similar risk factors, they have different etiologies, 7 so it is important to investigate the pathogenesis and prognostic factors for LAA-type stroke compare with other type of stroke. 6 Although most subtypes of ischemic stroke share similar risk factors, they have different etiologies, 7 so it is important to investigate the pathogenesis and prognostic factors for LAA-type stroke compare with other type of stroke.…”
mentioning
confidence: 99%